Teacher Resilience and Learning Innovation Measurement: Exploring the Moderating Effects of Knowledge Sharing and Openness to Experience - Yohamintin, Yohamintin (JURNAL AL-TANZIM, 2023)
This study aims to determine the level of openness to experience and knowledge sharing on learning innovation and teacher resilience affected by the eruption of Mount Semeru in Lumajang Regency, East Java Province. This research is a non-experimental quantitative research with a survey design. A total of 180 teachers selected by purposive sampling participated in this survey research. The data that has been collected was then analyzed using the WARP PLS 7.3 application and the IBM Statistical Package for Social Science (SPSS) version 23 application. The results of the analysis using WARP PLS 7.3 found values indicating that: 1) teacher resilience has an effect on knowledge sharing of 74.4 %., 2) teacher resilience has an effect on openness to experience of 71.6%. 3) teacher resilience has no effect on innovation learning. 4) knowledge sharing has an effect on innovation learning by 28.6%. 5) openness to experience affects innovation learning by 66.4%. 6) teacher resilience has an effect on innovation learning through knowledge sharing of 44.0%. This means that knowledge sharing can become a mediator variable in influencing the innovation learning model of the teacher resilience variable. 7) teacher resilience has an effect on innovation learning through knowledge sharing of 66.8%. This means that openness to experience is able to become a mediator variable in influencing innovation learning from teacher resilience variables.